Close Collaboration with Parents Affects the Length of Stay and Growth in Preterm Infants: A Register-Based Study in Finland - Itoshima, Ryo (Karger Publishers, 2025)
Introduction: This study aimed to evaluate how Close Collaboration with Parents (CC), a neonatal intensive care unit (NICU)-wide educational model for healthcare staff to improve their family-centred care practices, affects the length of stay (LOS), growth, and later hospital visits and rehospitalizations of preterm infants.
Methods: This register-based study included all preterm infants born below 35 weeks of gestation in Finland from 2006 to 2020. Eligible infants were classified into the Full Close Collaboration (Full-CC) group (n = 2,104) if the NICUs of both the delivery and discharge hospitals had implemented the intervention; into the Partial-CC group (n = 515) if only one of the NICUs had implemented the intervention; and into the control group (n = 11,621) if neither had implemented the intervention.
Results: The adjusted LOS, the primary outcome, was 1.8 days or 6% shorter in the Full-CC group than in the control group (geometric mean ratio 0.94, 95% confidence interval [95% CI] 0.89-1.00). Growth was better in the Full-CC group compared to the control group: adjusted group difference 11.7 g/week (95% CI, 1.4-22.0) for weight, 1.3 mm/week (95% CI, 0.6-2.0) for length. The Full-CC group infants had lower odds of having any unscheduled outpatient visits compared to the control group (adjusted odds ratio 0.81; 95% CI, 0.67-0.98). No significant differences were found in any other comparisons.
Discussion/conclusion: The unit-wide intervention improving family-centred care practices in NICUs may lead to more efficient use of hospital resources by shortening the LOS, improving growth, and decreasing hospital visits of preterm infants.